Pengaruh Kepuasan Kerja dan Lingkungan Kerja Terhadap Loyalitas Karyawan pada PT Xyz - Anne Dena Ganera; Harry Sardjono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of job satisfaction and work environment on employee loyalty. This type of research used in this study is to use quantitative methods. In this study, researchers used quantitative data from the results of distributing questionnaires via google form. The sample of this research is as many as 30 respondents in PT XYZ. Measurement of variables for hypothesis testing using the T test and F test. In testing the hypothesis, it is known that the value of tcount <ttable is 0.826 <2.04427 with a significance value of job satisfaction of 0.416> 0.05, which means that job satisfaction (X1) has no significant effect on PT XYZ. , tcount <ttable, namely 4.117> 2.044. With a significance value of 0.000 <0.05, it means that it has a positive and significant effect on Employee Loyalty, the F value of 9.573> F table 3.34 with a significance value of 0.001 <0.05. It can be concluded that H3 is accepted, meaning that there is a simultaneous influence of Job Satisfaction and Work Environment on Employee Loyalty.